2005
DOI: 10.1590/s0074-02762005000400006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human T-cell lymphotropic virus coinfecting human immunodeficiency virus 1 infected patients in the Amazon region of Brazil

Abstract: The present work evaluated the epidemiology of human immunodeficiency virus 1/human T-cell lymphotropic virus (HIV-1/HTLV) coinfection in patients living

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
1
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
4
21
1
6
Order By: Relevance
“…The detection of HTLV-1, Cosmopolitan Group, Transcontinental subgroup is in agreement with other studies that indicate its presence in the rural area of the state of Pará (Vallinoto et al 2004, Laurentino et al 2005 Rooted phylogenetic tree, showing the evolutionary relationship of human T-cell lymphotropic virus 1 strains described thus far including newly sequenced isolates from the present study (SNT43 and SNT92). The tree was constructed by the Neighbour-Joining method after alignment of 489 nucleotides of the 5'LTR region.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The detection of HTLV-1, Cosmopolitan Group, Transcontinental subgroup is in agreement with other studies that indicate its presence in the rural area of the state of Pará (Vallinoto et al 2004, Laurentino et al 2005 Rooted phylogenetic tree, showing the evolutionary relationship of human T-cell lymphotropic virus 1 strains described thus far including newly sequenced isolates from the present study (SNT43 and SNT92). The tree was constructed by the Neighbour-Joining method after alignment of 489 nucleotides of the 5'LTR region.…”
supporting
confidence: 93%
“…It was not possible to obtain PBMC from the samples of Ponta de Pedras village. The molecular characterization of HTLV-1 and HTLV-2 infection was performed by nested PCR and RFLP typing of the pX, env and 52 LTR segments using sets of primers, as previously described (Hall et al 1992, Tuke et al 1992, Laurentino et al 2005. Amplified fragments of 52 LTR were purified and sequenced according to a protocol previously reported (Laurentino et al 2005).…”
mentioning
confidence: 99%
“…The positional nomenclature of the tax region corresponds to sequence alignment with ATK strain Tax gene 7401 7914 7920 7982 8231 Isolates TSP165 T C T T A A TSP168 T C T T A A TSP23 T C T T A A TSP33 T C T T A A TSP124 T C T T A A TSP126 C T T T A A TSP262D T C T T A A TSP261 T C T T A A TSP318B C T T T A A AS174E T C T T A A AS230B T C T T A A AS257 T C T T A A AS368 T C T T A A AS232D T C T T A A using RFLP on samples from the LTR region, that the majority of patients from São Paulo belonged to the Cosmopolitan A subtype, although other LTR subtypes are also present in this population (Yamashita et al 1999, Segurado et al 2002. The mere detection of tax sub-strain A in our cohort and the high prevalence of viral infection among the African descendents in the North and Northeast of the country (Bendelt et al 2001, Alcantara et al 2003, Laurentino et al 2005) support the hypothesis that the Brazilia...…”
Section: Discussionmentioning
confidence: 70%
“…Certain evolutionary studies suggest that the first introduction of the virus in the continent occurred with the migration of the Mongol population through Bhering Straits around 40,000 to 10,000 years ago. Other studies suggest that the virus was brought along with the postColumbian African slave trade around 400 years ago, or more recently, due to migrations of HTLV-1 infected Japanese immigrants to Latin America as previously reviewed (Laurentino et al 2005). …”
Section: Discussionmentioning
confidence: 78%
“…The investigation of Brazilian HTLV-1 isolates from different regions and ethnic groups showed that the epidemic is more homogeneous than that of HIV-1, and is characterized by the presence of HTLV-1 Cosmopolitan subtype, Transcontinental subgroup, throughout Brazil (Liu et al 1996, Yamashita et al 1999, Alcantara et al 2003, Zehender et al 2004, Vallinoto et al 2004, Laurentino et al 2005, Alcântara et al 2006.…”
mentioning
confidence: 99%